2010
DOI: 10.1002/aic.12407
|View full text |Cite
|
Sign up to set email alerts
|

pH-responsive hydrogel microparticles as intelligent delivery carriers for α-MSH antagonists

Abstract: For a first step in the development of an intelligent delivery system for a nonapeptide as an a-MSH antagonist, pH-responsive P(MAA-co-EGMA) hydrogel microparticles were prepared and their feasibility as intelligent delivery carriers was evaluated. There was a drastic change in the swelling ratio of P(MAA-co-EGMA) microparticles at a pH of around 5 and as the MAA amount in the hydrogel increased, the swelling ratio increased at a pH above 5. The loading efficiency of the nonapeptide at pH 7 increased with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The upper limit is determined using a restrictive criterion such that the continuum-plus-excited-state contributions are less than about 30% of the phenomenological side, which is imposed so as to warrant the pole dominance. Using these criteria we have similarly found that the sum rule in (9) has a valid Borel window while those in (10) and (11) are seriously contaminated by continuum contributions. Therefore we choose to work with the sum rule at the structure iZ µ σ µν p ν γ 5 in (9).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The upper limit is determined using a restrictive criterion such that the continuum-plus-excited-state contributions are less than about 30% of the phenomenological side, which is imposed so as to warrant the pole dominance. Using these criteria we have similarly found that the sum rule in (9) has a valid Borel window while those in (10) and (11) are seriously contaminated by continuum contributions. Therefore we choose to work with the sum rule at the structure iZ µ σ µν p ν γ 5 in (9).…”
Section: Resultsmentioning
confidence: 95%
“…Actually, this result is supported by some model-dependent approaches as well (see Appendix A). An investigation of this interesting issue has the potential to shed light on the "spin crisis" and therefore attracted considerable attention [7,8,9,10,11,12]. Experimentally, the polarization of Λ is of special interest because it can be easily measured from the nonleptonic decay Λ → p π [13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To control microneedle properties, PEGDMA was copolymerized with VP. PEGDMA was used as a second monomer because it has a good biocompatibility, is liquid in monomeric form, can make a cross-linked network after polymerization, and has been used for pharmaceutical purpose for a long time [23][24][25]. The mechanical strength of the fabricated microneedles was tested by applying different loads onto the microneedles and calculating the remaining length ratio, defined as the ratio of the final length of the deformed needle to the length of the original needle.…”
Section: Characterization Of Pvp Microneedlesmentioning
confidence: 99%